Relationship Marketing among Coconut Sugar Traders, Main Suppliers, and Main Customers - Salam, Rudhiana; Primary, Metty Agustine; Rahmat (Nusantara Science and Technology Proceedings, 2025)
This study aims to analyze relationship marketing among coconut sugar traders in Tonjongsari Village, Cikalong District, Tasikmalaya Regency, West Java, and their main suppliers and customers. The analytical method used is the Wilcoxon Signed Ranks Test, which is suitable for paired ordinal data. Data were collected through questionnaires and analyzed using SPSS 26 software. The analysis results show significant differences in the dimensions of trust, satisfaction, and dependence between suppliers and customers, with significance values of 0.038, 0.018, and 0.031, respectively, while the commitment dimension did not show a significant difference (0.713). The categorization results indicate that all relationship marketing dimensions are in the high category, both for the traders' perceptions of the main suppliers and customers. This study concludes that traders have better relationships with customers than with suppliers in terms of trust, satisfaction, and dependence, although commitment did not show significant differences. These findings provide insights for improving relationship marketing strategies in the future.